Protocol summary and statistical analysis plan for Intensive Nutrition Therapy comparEd to usual care iN criTically ill adults (INTENT): a phase II randomised controlled trial. Issue 3 (8th March 2022) - Ridley, Emma J; Bailey, Michael; Chapman, Marianne; Chapple, Lee-anne S; Deane, Adam M; Hodgson, Carol; King, Victoria L; Marshall, Andrea; Miller, Eliza G; McGuinness, SP; Parke, Rachael; Udy, Andrew A
Abstract : Introduction: It is plausible that a longer duration of nutrition intervention may have a greater impact on clinical and patient-centred outcomes. The Intensive Nutrition care Therapy comparEd to usual care iN criTically ill adults (INTENT) trial will determine if a whole hospital nutrition intervention is feasible and will deliver more total energy compared with usual care in critically ill patients with at least one organ system failure. Methods and analysis: This study is a prospective, multicentre, unblinded, parallel-group, phase II randomised controlled trial (RCT) conducted in 23 hospitals in Australia and New Zealand. Mechanically ventilated critically ill adult patients with at least one organ failure who have been in intensive care unit (ICU) for 72–120 hours and meet all of the inclusion and none of the exclusion criteria will be randomised to receive either intensive or usual nutrition care. INTENT started recruitment in October 2018 and a sample size of 240 participants is anticipated to be recruited in 2022. The study period is from randomisation to hospital discharge or study day 28, whichever occurs first, and the primary outcome is daily energy delivery from nutrition therapy. Secondary outcomes include daily energy and protein delivery during ICU and in the post-ICU period, duration of ventilation, ventilator-free days, total bloodstream infection rate and length of hospital stay. All other outcomes are considered tertiary and results will be analysed on an intention-to-treat basis. Ethics and dissemination: Ethics approval has been received in Australia (Alfred Hospital Ethics Committee (HREC/18/Alfred/101) and Human Research Ethics Committee of the Northern Territory Department of Health (2019-3372)) and New Zealand (Northern A Health and Disability Ethics Committee (18/NTA/222). Results will be disseminated in an international peer-reviewed journal(s), at scientific meetings and via social media. Trial registration number: NCT03292237 .